Interactive Learning Media With Augmented Reality (AR) Geogebra for Teaching Geometry in Elementary School - Buchori, Achmad; Sulianto, Joko; Osman, Sharifah (Profesi Pendidikan Dasar, 2023)
In Semarang's elementary maths education, augmented reality (AR) and three-dimensional tech are underused in geometry instruction. These technologies promise an engaging and interactive presentation of three-dimensional objects. Presently, educators are confined to traditional tools like PowerPoint, providing a less immersive learning experience. This study addresses this gap with AR Geogebra, a tailored interactive tool for geometry instruction. Developed using the ADDIE model, the study involved fifty fifth-semester university students. Notably, material and media validation scored 90%, deeming it "extremely valid." Practicability, assessed by the experimental class and subject teacher, reached 90%, indicating high practicability. Post-test results showed an N-gain of 0.39 for the exposed group, surpassing the control group's 0.02. In conclusion, AR Geogebra proves an effective pedagogical approach for geometry instruction in elementary maths education.